Three non-centrosymmetric bismuth phosphates, Li2ABi(PO4)2 (A = K, Rb, and Cs): effects of cations on the crystal structure and SHG response. Issue 18 (5th August 2020) - Wen, Ming; Hu, Cong; Wu, Hongping; Yang, Zhihua; Yu, H. H.; Pan, Shilie
Abstract : We reported the synthesis, structure and nonlinear properties of three phosphates, Li2 ABi(PO4 )2 (A = K, Rb, and Cs), and the effects of cations on the crystal structure and SHG response. Abstract : Three new bismuth phosphates, Li2 ABi(PO4 )2 (A = K, Rb, and Cs), were synthesized through the high-temperature solution method. They all exhibit three-dimensional (3D) [Li2 P2 O8 ] 4− frameworks built by isolated PO4 tetrahedra and Li–O chains but crystallize in two different space groups, which can be attributed to the effects of alkali metal cations that control the connection modes of units. Li2 KBi(PO4 )2, Li2 RbBi(PO4 )2 and Li2 CsBi(PO4 )2 show SHG intensities about 5.0, 3.1 and 2.5 times that of KDP, respectively, and are all phase-matchable. To the best of our knowledge, Li2 KBi(PO4 )2 exhibits the largest SHG response among the bismuth phosphates. The effects of cations on the SHG responses have been discussed in detail. Our results indicate that introduction of the Bi 3+ cation with large distortion and synclastic arrangement of the Bi–O polyhedra is crucial to produce the large SHG response for phosphate NLO materials.